2016
DOI: 10.1515/limre-2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the trophic status of lakes in the Suwałki Landscape Park (NE Poland)

Abstract: Abstract:Summer field research and chemical analyses in 2015 provided the basis for the presentation of the trophic status of waters of 28 lakes of the Suwałki Landscape Park in NE Poland, located in the catchment of the River Neman, in the Natura 2000 area -Ostoja Jeleniewska. Lakes Hańcza and Szurpiły are currently mesotrophic ecosystems. The remaining lakes are moderately eutrophic, while four lakes in the group, in addition to anaerobic hypolimnion, have infertile epilimnion similar to that of mesotrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…Correlations made for the number of rotifer species versus trophic state indices and chemical (acc. to Górniak et al 2016) and biological data for the set of lakes studied in 2015 (Figs 2-5) revealed only four significant relationships. There was a significant (p = 0.009) relationship between trophic state index (TSI) calculated from mean values of total phosphorus and chlorophyll-a (acc.…”
Section: Resultsmentioning
confidence: 94%
“…Correlations made for the number of rotifer species versus trophic state indices and chemical (acc. to Górniak et al 2016) and biological data for the set of lakes studied in 2015 (Figs 2-5) revealed only four significant relationships. There was a significant (p = 0.009) relationship between trophic state index (TSI) calculated from mean values of total phosphorus and chlorophyll-a (acc.…”
Section: Resultsmentioning
confidence: 94%
“…Analysis of the mean values using the Kruskal-Wallis ANOVA test did not show that the conductivity differences between the time series considered were statistically significant (p = 0.154), similarly to the pair comparison (Mann-Whitney U test; p = 0.124). 1934-1935 and 1975 were estimated from the conductivity-bicarbonate statistical model based on data from [35,36] and [37], values for 2015 according to [43].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the long-term trends of selected optical characteristics of SLP lake water, the unpublished results of the authors' hydro-optical measurements performed in the years 1997-2016 were used, together with the materials available in the literature (Koźmiński 1932;Stangenberg 1936Stangenberg , 1937Szczepański 1961;Gór-niak et al 2007;Zdanowski 2008;Jekatierynczuk-Rudczyk et al 2014;Górniak et al 2016).…”
Section: Research Area and Methodsmentioning
confidence: 99%